The knowledge level of retail pharmacists in elazi? and Malatya on emergency contraception - Sevindik, Feyza; Omaç, Mehtap; Güneş, Gülsen; Açik, Yasemin (University of Ankara, 2007)
Pharmacists have a key role in family planning and emergency contraception. The aim of this study is to determine the knowledge level of pharmacists in Elazi? and Malatya on emergency contraception. There are 190 pharmacies in Elazi? and Malatya. In this study no sampling technique was used, instead it was aimed to reach all the pharmacists. Pharmacists were given a questionnaire having two sections. In the first section, there are statements related to socio-demographic characteristics and in the second section there are questions including knowledge levels and opinions of pharmacists relating to family planning methods and emergency contraceptive pills (ECP) available in the pharmacy and there are statements in which pharmacists asses their knowledge of planned parenthood methods. 154 pharmacists were reached with the help of repetitious visits. The average age of pharmacists included in the study was 37.70±10.20 and working years pharmacists were 12.28±8.98. % 52.6 of the pharmacists was male and, % 59 of them was married. Pill and condom % 85.1 and ECP % 74.7 were available in the pharmacies. The most demanded methods were pills (% 79.9), condoms (% 59.1) and ECP (% 35.1). % 96.8 of pharmacists stated that they have knowledge on emergency contraception and % 90.9 of them stated that they have ECP in their pharmacies. The rate of the pharmacists stating that the component of the ECP used in emergency contraception is same as birth control pills was % 15.4. The rate of pharmacists answering correct to "when to use ECP" is % 55. The more working years pharmacists have the less correct answers are given to the question of "how soon ECP can be taken after the sexual intercourse" (p<0.05). The knowledge level of retail pharmacists was found to be less although they sell these pills in their pharmacy. Training aimed to improve the counseling skills of pharmacists related to this topic should be planned.
Elazi? ve Malatya i?lleri?nde eczacilarin aci?l kontrasepsi?yonla i?lgi?li? bi?lgi? düzeyleri?
Keywords: Elazi?; Emergency contracepsion; Level of knowledge; Malatya; Pharmacist